A critical study on the role of SUHAKAM in promoting human rights in Malaysia / Sara Adila Idrose, Wan Azira Wan Khairilanwar and Alia Sumayyah Amran. - Idrose, Sara Adila; Wan Khairilanwar, Wan Azira; Amran, Alia Sumayyah (2011)
The Malaysian Human Rights Commission or SUHAKAM, which is the famous term for this institution, is a national human rights institution, or rather, many would say, infamous. This is because, SUHAKAM is seen as "toothless tiger." To the public eye and other human rights bodies, the functions of SUHAKAM are merely the government's agenda to be seen as proactive in the human rights sphere. These claims are analysed in the progression of this research. This research aims at finding the underlying problem that caused such claims on SUHAKAM to surface. It is embodied within the research that the powers conferred by the Human Rights Commission Act 1999 and the method of appointment of SUHAKAM should be altered so to reflect that, "justice should not only be done, but should be seen to be done." On this basis, many articles, journals and papers written by professional academician and writers are used as reference to critically analyse the extent of the effectiveness of Human Rights Commission and the mode of appointment of the members of the Commission. Reference is also made to current reports by SUHAKAM including relevant international report that could contribute to the development of this research Public view are also been taken into consideration to evaluate the acceptance and effectiveness of the Commission from the eyes of the public. Each chapter is organized systematically providing issues and evidence of each claim. This research also comprises of comparison to Human Rights Commission in India.